2018
DOI: 10.1002/smll.201801423
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Nucleation in Lithium Metal Anodes

Abstract: Rechargeable batteries are regarded as the most promising candidates for practical applications in portable electronic devices and electric vehicles. In recent decades, lithium metal batteries (LMBs) have been extensively studied due to their ultrahigh energy densities. However, short lifespan and poor safety caused by uncontrollable dendrite growth hinder their commercial applications. Besides, a clear understanding of Li nucleation and growth has not yet been obtained. In this Review, the failure mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
132
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 184 publications
(143 citation statements)
references
References 140 publications
4
132
0
2
Order By: Relevance
“…[1,13] 2) Infinite volume fluctuation of Li anodes brings serious damage to the fragile solid electrolyte interphase (SEI), and causes unstable Li anode/liquid electrolyte interface during Li plating/stripping. [15] To effectively address the aforementioned problems, numerous strategies have been proposed, including structured anode design, [16][17][18][19] in/ex-situ artificial SEI protective layer, [20,21] functional electrolyte additives, [22,23] and solid/quasisolid-state electrolytes. [15] To effectively address the aforementioned problems, numerous strategies have been proposed, including structured anode design, [16][17][18][19] in/ex-situ artificial SEI protective layer, [20,21] functional electrolyte additives, [22,23] and solid/quasisolid-state electrolytes.…”
mentioning
confidence: 99%
“…[1,13] 2) Infinite volume fluctuation of Li anodes brings serious damage to the fragile solid electrolyte interphase (SEI), and causes unstable Li anode/liquid electrolyte interface during Li plating/stripping. [15] To effectively address the aforementioned problems, numerous strategies have been proposed, including structured anode design, [16][17][18][19] in/ex-situ artificial SEI protective layer, [20,21] functional electrolyte additives, [22,23] and solid/quasisolid-state electrolytes. [15] To effectively address the aforementioned problems, numerous strategies have been proposed, including structured anode design, [16][17][18][19] in/ex-situ artificial SEI protective layer, [20,21] functional electrolyte additives, [22,23] and solid/quasisolid-state electrolytes.…”
mentioning
confidence: 99%
“…[26] The graphite-SiO 2 bilayer (Figure 2b) protects the bare Li from any side reactions. [27] These protuberances generate nonuniform electric field during charge/discharge leading to inhomogeneous plating of Li. The cracks and uneven surface can be seen in high-resolution AFM images in Figure 2c,e for the bare Li metal surface.…”
Section: Resultsmentioning
confidence: 99%
“…Atomic force microscopy (AFM) was used to study the surface topography and measure Young's modulus mapping of bare Li and graphite-SiO 2 Li. [7c, 27,28] Local high electric field and high lithiumion flux accelerate nucleation and growth of Li at the local points which gradually change into the dendritic Li. The surface roughness values of the bare Li and graphite-SiO 2 Li were compared by measuring the average surface root mean square (RMS) via high-resolution AFM.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were aimed at developing large surface area porous hosts to reduce the local current density and thus inhibit dendrite formation according to the classical theory of dendrite growth . However, recent studies have shown that porous hosts with a large electroactive surface area are helpful in reducing the nucleation overpotential and producing uniform Li deposition . Therefore, attention needs to be paid to the nucleation behavior of Li within the host to further regulate Li deposition and improve the cycling performance of the Li anode.…”
Section: Strategies For Developing Stable LI Metal Anodesmentioning
confidence: 99%
“…Li is an extremely reactive metal having only one electron in its outer shell, and due to the shielding effect between the nucleus and the inner electrons, it can easily loss its outer electron to form Li + , making it highly reactive and thermodynamically unstable. [19] Furthermore, rechargeable batteries are usually operated at a constant current density with an equal amount of current flowing between the two opposite electrodes (I cathode = I anode ). As the positive electrode is usually porous in nature, the electric field is uniformly distributed and the current density is normalized by its relatively high electroactive surface area.…”
Section: Reactivity Of LI Metalmentioning
confidence: 99%